Can the bishop prohibit marriages outside a church Canon 1118 - Huels, John M. 1950- (2006)
A policy in our diocese prohibits all marriage outside the church or oratory, including non-sacramental marriages. Also, the bishop will not give a dispensation from canonical forn unless the parties agree to have their marriage in a church, synagogue, mosque or similar sacred edifice. Is this policy in keeping with the universal law?
Keywords: Katholische Kirche; Eherecht; Dispens; Bischof; Eheschließungsort; Formpflicht